"They think you are weak": Examining the Drivers of Gender-Based Violence in Three Urban Informal Settlements. (April 2022) - Maclin, Beth J.; Bustamante, Nirma D.; Wild, Hannah; Patel, Ronak B.
The global trend of rapid urbanization raises concerning issues related to the living standards of the urban poor, many of whom live in dense informal settlements. Residents of informal urban settlements can face significant insecurity, with men and women experiencing different threats. While space and socioeconomic status have specific consequences on the hazard of violence that urban residents face, gender modifies the impact of that violence. In an attempt to understand the drivers of insecurity within a social ecological framework, this study investigated underdeveloped neighborhoods in Addis Ababa, Ethiopia; Dhaka, Bangladesh; and Port-au-Prince, Haiti. The qualitative approach employed focus group discussions using various probing techniques and key informant interviews followed by a thematic analysis of the data. The direct quotes and experiences of young and older women compared to those of young and older men highlight how the combination of factors - gender and poverty - drive differential risk for women compared to men among the urban poor in these cities.